Effect of Synthesis Condition on the Structural and Magnetic Parameters of Ni Ferrite: Investigating the Influence of Synthesis Condition on the Structural and Magnetic Properties of Nanosized Nickel Ferrite (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Nanosized nickel ferrite powders (NiFe2O4) have been prepared by solid-state reaction method at different temperature 900oC(T1) and 1100oC (T2) for 4h. The resulting powders were characterized by Xray diffraction (XRD) and vibrating sample magnetometry (VSM). The powder samples T1 and T2 showed extensive XRD line broadening and the crystallite size calculated from the XRD line broadening was found to be 52.21 nm and 59.60 nm respectively. The saturation magnetization was obtained 43.82emug and 63.34emug for samples T1 and T2 respectively.